(untitled) (Tạp chí Y học Cộng đồng, 2026)
Background: Overweight and obesity among children and adolescents are rapidly increasing and have become a major global public health concern, including in Vietnam. This condition not only affects physical development but also increases the risk of chronic diseases and negatively impacts psychological well-being. In urban settings, particularly in international school environments, the risk may be higher due to sedentary lifestyles and dietary changes. This study aimed to determine the prevalence of overweight and obesity and to describe selected characteristics among secondary school students at the International School of Ho Chi Minh City (ISHCMC). Methods: A cross-sectional study was conducted among 151 students aged 11–15 years. Anthropometric measurements, including weight and height, were obtained using standardized procedures, and body mass index (BMI) was calculated. Nutritional status was classified according to the WHO 2007 growth reference using BMI-for-age Z-scores. Data were analyzed using STATA version 14.0. Descriptive statistics were used, and statistical significance was set at p < 0.05. Results: The overall prevalence of overweight and obesity was 33.1%, including 19.9% overweight and 13.2% obes ity. The mean BMI was 21.1 ± 4.5 kg/m². Male students had significantly higher mean weight and height compared to females (p < 0.05), while no significant difference in BMI was observed between sexes. The prevalence of overweight and obesity was higher in males than in females. Conclusions: The prevalence of overweight and obesity among secondary school students in an international school setting is relatively high, reflecting a clear nutritional transition. Early interventions targeting school environments are necessary to address this issue.